Rendahnya kesadaran mahasiswa terhadap kewajiban belajar: analisis tantangan dalam dunia perguruan tinggi - Anas sh, Moh Azwar (Maliki Interdisciplinary Journal, 2026)
This study focuses on analyzing the elements that influence the low level of learning awareness among students in higher education. This issue is crucial because learning awareness is a crucial component in determining their academic success. The method applied in this study was a quantitative approach by conducting a survey, namely distributing questionnaires to 31 students as respondents. The variables analyzed included internal factors such as learning motivation and time management, as well as external factors related to social media use, with learning awareness as the dependent variable. The results of the analysis indicate that students’ academic awareness is categorized as quite high. Motivation to learn among students is relatively high, but this is not in line with effective time management skills. In addition, the presence of social media also affects students’ learning concentration, although it is not the main factor. Based on the existing findings, it can be concluded that low learning awareness among students is not only triggered by a lack of motivation, but is more influenced by poor time management and distractions from social media. This research is expected to contribute to improving the quality of the student learning process in higher education..